Implementasi Waktu dalam Pengembangan Keterampilan sebagai Awal Mula Ide Bisnis bagi Adik-Adik Panti Asuhan - Anggraini, Dewita Rana; Barkah, Barkah; Febriandi, Rieqa Adzelia; Wati, Syf Marfirah; Riantika, Naswa; Febriana, Febby (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The aim of this community service activity is to introduce and explore the implementation of time management in developing business skills for orphanage residents. Children in orphanages often lack adequate access to education and skills training. Through the application of structured training on effective time management, this program provides opportunities for orphanage children to develop practical skills, including entrepreneurial skills. This activity was conducted at the Catur Dharma Orphanage, Pontianak, using observation and interview methods to collect data. The results of this activity indicate that good time management positively impacts the productivity of training participants, enabling them not only to improve technical skills but also to formulate business ideas based on the skills they have learned. This community service activity recommends repetitive skill training focused on entrepreneurship and time management to enhance the independence of orphanage children, which is expected to create sustainable business opportunities for them.